Diversi Sebagai Bentuk Penyelesaian Perkara Anak Yang Berhadapan Dengan Hukum (Studi Putusan Perkara Nomor 3/Pid.Sus-Anak/2022/PN Amb) - Latekay, Honney Uplera; Wadjo, Hadibah Zachra; Corputty, Patrick (PATTIMURA Law Study Review, 2024)
ABSTRACT: Diversion is the transfer of resolution of children's cases from the criminal justice process to a process outside criminal justice. Diversion is carried out at three levels, namely at the investigation, prosecution and court levels. In this case, if the diversion deliberation process is successful, the case will not proceed to the next stage, but if diversion deliberations fail to be carried out at the investigation level, the next effort is to conduct diversion deliberations at the prosecution level. If there is no common ground at the prosecution level, then diversion will be attempted at the court level. The aim of this research is to find out whether the diversion process in this research has fulfilled the principle of legal certainty or not and to find out what factors cause the success of diversion in court. Based on the results of this research, it was concluded that it does not fulfill the principle of legal certainty, because children who make mistakes are not given a deterrent effect by being sentenced to 15 years in prison as regulated in article 81 paragraph (1) and/or paragraph (2) Jo. Article 76D of Law number 35 of 2014 is an amendment to Law 23 of 2002 concerning child protection and the factors causing the success of diversion in court, namely consideration of the customs of Supreme Court Regulation No. 4 of 2014 Article 3.